Estimating of bearing capacity of subsoil under shallow foundations related to European Standards - Nepelski, Krzysztof (Budownictwo i Architektura / Civil and Architectural Engineering, 2013)
paper presents the calculation method of bearing capacity based on European Standards. The analysis of bearing capacity depends on the strength parameters of soil. Results were presented as a graph "bearing capacity" - "strength parameter". All of the results were compare to Polish Standards. Minimal dimensions of foundation were calculated for every bearing capacity. The design value of an action was calculated on the basis of European and Polish Standards.